Prevalence and associated risk factors of chronic kidney disease: A case study within SIME clinics in Quito, Ecuador 2019–2021 - Eguiguren-Jiménez, Lucía; Miles, Joshua; Ocampo, Jaime; Andrade, Jeanette Mary (Frontiers in Medicine, 2022)
Background: Ecuador has been experiencing an epidemiological transition due to its demographic and lifestyle changes, where non-communicable diseases are the leading cause of death, including chronic kidney disease (CKD). Quito, Ecuador’s capital city, is one of the cities burdened by CKD, yet it is unknown the factors that contribute to the rising incidence of this disease. The purpose of this study was to estimate the prevalence of CKD among non-institutionalized adults in Quito between 2019-2021, and to examine its associations with various risk factors. Methods: For the analysis of prevalence, the Kidney Disease: Improving Global Outcomes guidelines were used, where an estimated glomerular filtration rate (eGFR) of < 60 ml/min/1.73 m2 was counted as a presumed case of CKD. The Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation was used to calculate eGFR. Multiple linear regression models were used to determined associations between blood pressure, blood glucose, sex, and zone with eGFR. A t-test of independence was used to determine difference in means between sex and zone and eGFR. Results: A prevalence of 7.2% was found, in which almost 45% of the participants were classified within stages 2-4 of this disease. The risk factors that were significantly associated with eGFR were systolic blood pressure (β=-0.43, p<0.001), sex, and zone (p<0.001). Conclusions: Overall a high prevalence of CKD was found among adults who visited SIME clinics in Quito. Associations between main risk factors and eGFR were found, yet further research is needed to explore CKD in Ecuador and its main cities.